KEEPING A BALANCE IN TEACHING GRAMMAR (Web of Teachers: Inderscience Research, 2023)
The article is devoted to the study of the importance of grammar in teaching language. The reasons for avoiding focusing more attention on it and at the same time strategies to keep crucial topics are investigated.